Subchondral Insufficiency Fracture of the Femoral Head Caused by Excessive Lateralization of the Acetabular Rim - Tetsuya Kimura; Tomohiro Goto; Daisuke Hamada; Takahiko Tsutsui; Keizo Wada; Shoji Fukuta; Akihiro Nagamachi; Koichi Sairyo (Case Reports in Orthopedics)
We present a case of a 53-year-old woman with subchondral insufficiency fracture (SIF) of the femoral head without history of severe osteoporosis or overexertion. Plain radiographs showed acetabular overcoverage with excessive lateralization of the acetabular rim. A diagnosis of SIF was made by typical MRI findings of SIF. The lesion occurred at the antipodes of the extended rim. Increased mechanical stress over the femoral head due to impingement against the excess bone was suspected as a cause of SIF. The distinct femoral head deformity is consistent with this hypothesis. This is the first report of SIF associated with acetabular overcoverage.